À flor da pele : experiência estética em uma feira livre de Vitória/ES - Ferreira, Tatiane Alves (2018)
The present dissertation draws on the theoretical approach of the organizational aesthetics to understand how aesthetic experiences are revealed in the flower trade in a street market. For that, I immersed body and soul in the field from July to September